Circular Economy in Agriculture: Examining Factors Affecting People's Intention to Use Organic Fertilizer - Risna Maya Sari; Karimi Karimi; Siti Yuli Meilanda Sormin (Universitas Labuhanbatu, 2025)
Examining the variables that affect people's intentions to use organic fertilizer in agriculture is the aim of this study. By identifying these factors, it is expected to provide a better understanding of what encourages or hinders people in using organic fertilizers. The findings of this study will significantly aid in the formulation of plans and regulations that can promote the use of organic fertilizers and the adoption of a circular economy in the field of agriculture. Methods This research is designed as an explanatory research that can explain the method of testing a theory to strengthen or reject the research hypothesis. Therefore, the explanatory approach is very suitable to be used in this research in accordance with the research objectives. The data in this study consisted of primary data collected using a questionnaire. To examine the behavioral components of this study, researchers employed the Partial Least Square (PLS) method in conjunction with Structural Equation Modeling (SEM). The urgency of this study arises from the pressing need to address environmental degradation, resource scarcity, and unsustainable agricultural practices. Therefore, it is important to implement agricultural practices that prioritize sustainability aspects, one of the solutions is the widespread use of organic fertilizers in the community. The study's findings indicate that farmers' intentions to utilize organic fertilizer are influenced by social, institutional, and economic factors